First Report of Microplastic Ingestion and Bioaccumulation in Commercially Valuable European Anchovies (Engraulis encrasicolus, Linnaeus, 1758) from the Romanian Black Sea Coast - Andreea-Mădălina Ciucă; Elena Stoica; Lucica Barbeș (Journal of Marine Science and Engineering)
Microplastics (<5 mm) are an emerging threat to marine ecosystems and organisms, including fish. Recent studies have ranked the Black Sea as one of the most plastic-polluted European seas. Although there is evidence of microplastic ingestion in various fish species in the Black Sea, data for the Romanian sector are still lacking. This study presents the first assessment of microplastic abundance, color, shape, and size in the gastrointestinal tract and gills of Engraulis encrasicolus (European anchovy) collected from different locations along the Romanian coast (NW Black Sea). Ingested plastics were identified using 10% potassium hydroxide (KOH) chemical digestion and analyzed under a stereomicroscope. We observed a high frequency of plastic ingestion, with up to 88% of anchovies containing microplastics (98.5%) and mesoplastics (1.5%), with a mean of 3.03 plastic items/individual, marking the highest reported abundance in the Black Sea. The most common types found were transparent fibers, within the size range of 330 µm–1 mm. Our assessment is the first to demonstrate microplastic contamination in commercial European anchovies from the Romanian coast. Further studies are required to completely understand the extent of microplastic pollution in Black Sea anchovies and its potential impact on both human health and the ecosystem.